Validación concurrente del proceso de fabricación de metformina 850mg tabletas - González Acosta, Jhonathan Israel (2018)
The objective of the present investigation was to concurrently validate the manufacturing process of Metformin 850 mg tablets, perform tests on humidity, appearance, bulk density, density per set, hausner index and compressibility, during the mixing phase; tests of appearance, friability, hardness, weight, average weight, and disintegration, during the compression phase. Three batches of 300,000 units each were evaluated, in each batch controls were made in the mixing and compression phase for which the validation of the manufacturing process of Metformin 850 mg tablets was considered; obtaining as a result in the controls in the mixing phase, a conformable appearance, humidity 2.57%, bulk density 0.640 g / mL, good fluidity with respect to the compressibility and hausner index; in the controls of the compression phase, the appearance was conformed, the dimensions were on average 19.1 mm in diameter and 7.0 mm in thickness, with respect to weight, the average Cp and cpk was greater than 1.33; cp 1.63 and cpk 1.50. The average hardness was 22.17 kp, the friability was 0.34%, the disintegration was 20 min and 56 s, the average weight was 1010.48 mg. It is concluded that the concurrent validation allowed to determine that the manufacturing process of Metformin 850 mg tablets, meets the specifications of the manufacturing protocol of the pharmaceutical laboratory